Description of Phloeosinus laricionis sp. n. (Coleoptera: Curculionidae, Scolytinae), a new bark beetle species from southern Europe - Faccoli, Massimo; Sidoti, Agatino (Zootaxa, 2013)
We describe a new species of pine bark beetle, Phloeosinus laricionis, associated with a pine decline recently affecting young plantations of Pinus nigra ssp. laricio Poiret growing on the Etna volcano, Sicily (South Italy). The new species is morphologically close to the group species of P. cedri Brisout, P. acatayi Schedl, and P. pfefferi Knížek, having all odd interstriae on the declivity of elytra bearing small, individual, sparse, more or less sharply pointed tubercles in males, or with smaller sparse blunt, nippled tubercles in females. While the other species of the same group live on cedars, the new species is the only Palaearctic Phloeosinus known from pine.